Analisis Kinerja Keuangan Retribusi Dan Pajak Parkir Pada Pemerintah Daerah Kota Palu - Kamarudin, Jamaludin (Forecasting : Jurnal Ilmiah Ilmu Manajemen, 2022)
This study aims to determine the effectiveness of levies and parking taxes in Palu City during 2015-2019 and the contribution of parking levies and taxes to Palu City's Original Regional Revenue (PAD) during 2015-2019. The results show that the effectiveness of parking levies and parking taxes in Palu City for the last five years, 2015 – 2019 is said to be ineffective with the percentage of effectiveness for five years, namely 53.41%. The contribution of parking fees and taxes for the last five years, starting from 2015 – 2019 shows that parking fees and parking taxes have contributed to PAD in Palu City with an average contribution value of 0.05%. And the growth rate of parking levies, parking taxes and local revenue of Palu City shows that the growth results with positive criteria and the average percentage value is 43.52%.